1992
DOI: 10.1109/26.168796
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid DS/SFH-SSMA with predetection diversity and coding over indoor radio multipath Rician-fading channels

Abstract: Abstruct-This paper investigates the bit error rate (BER) performance of hybrid direct-sequence/slow-frequency-hopped spread-spectrum multiple-access (DS/SFH-SSMA) systems operating over a multipath Rician-fading channel (which models indoor radio propagation in factories). We consider both phaseshift-keying (PSK) modulation with coherent demodulation and differential phase-shift-keying (DPSK) modulation with noncoherent demodulation. Predetection multipath diversity (maximal ratio combining (MRC) for coherent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…is the total MAI term, where is the number of nonreference users that collide with the reference user in frequency . Assuming the hopping patterns of different users are mutually independent, has a binomial distribution with probability density function (pdf) given by (13) where is the probability that a nonreference user hits the reference user and approximates to for SFH [8]. Note that (13) also applies to the pure DS and the MC DS systems, i.e., , due to for these two systems.…”
Section: Performance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…is the total MAI term, where is the number of nonreference users that collide with the reference user in frequency . Assuming the hopping patterns of different users are mutually independent, has a binomial distribution with probability density function (pdf) given by (13) where is the probability that a nonreference user hits the reference user and approximates to for SFH [8]. Note that (13) also applies to the pure DS and the MC DS systems, i.e., , due to for these two systems.…”
Section: Performance Analysismentioning
confidence: 99%
“…However, the algorithm usually needs 10 to 20 symbol intervals to converge. An alternative resort is the frequency hopping (FH) technique [8], [9], in which the signal occupies only one subchannel at any interval and hops in frequency. By reducing the number of simultaneous cochannel users, FH systems have a natural guard against the near-far problem.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this class of CWCs, in fact, includes number of orthogonal intercodes, each activating a single carrier in one of the possible positions. Since the cross correlation between two intracodes is 1, the UUB of the intracode error probability conditioned on the tap attenuations can be expressed using (13) as (16) where is the -function defined as [19] and represents the average signal-to-noise ratio (SNR) for a certain , which is given by (17) while -the sum of squares of Nakagami distributed variables describing the multipath components' attenuations-is expressed as (18) The average UUB probability of intracode errors for a given is calculated from the conditional upper bound upon weighting by the pdf of , , and then averaging or integrating the weighted product over its legitimate range. Since is a sum of squares of Nakagami distributed variables with densities , as seen in (3), can be approximated [11] as the square of another Nakagami random variable, whose density is given by (19) where and .…”
Section: A Approach Imentioning
confidence: 99%
“…By contrast, the UUB of an intercode error for a given and conditioned on the tap attenuations can be written as (22) Similarly, the average UUB of the intercode error can be derived, following the approach of the average UUB of the intracode error computation, yielding (23) where is given by (21). Hence, the UUB of the error probability per bit for a given number of hits is the sum of (20) and (23), which is given by (24) Finally, the average UUB of bit-error probability (BER) can be expressed as [17], [18] (25) where and is given by (24) and is the probability of a hit-as defined previously-from an interfering signal. In an asynchronous system, can be approximated as (26) where is the average weights of the constant-weight codewords used in the system.…”
Section: A Approach Imentioning
confidence: 99%
“…It was shown that blind joint soft-detection can achieve the required bit-error-rate (BER) performance, while blindly acquiring the FH patterns employed. In this treatise, we study a FH/MC DS-CDMA system employing slow FH [10], [11]-resulting in a SFH/MC DS-CDMA system-and binary modulation. The system operates in a multipath fading environment, and a maximum ratio combining (MRC) assisted RAKE receiver is used.…”
Section: Introductionmentioning
confidence: 99%